New challenges to rethink the training of ecuadorian teachers - María Sol Villagómez (Universidad Politécnica Salesiana, 2012)
Training ecuadorian teachers has traditionally been linked to public policy and national curricula that have defined the task of teaching, classroom work, and what basic teacher training institutions should prioritize on when it comes to training teachers. Recent years have seen major changes in the educational sector, as well as a revaluation of the teaching trade. New training challenges arise, not only from the teacher's perspective as executor of the curricula, but as a key player in the educational process. We need to rethink the training of teachers to and from a critical reflection and research point-of-view, in order to reflect on the curricula, their own experience, and their relevance in relation to the framework in wich they develop.